A control strategy for multiphase series capacitor boost converter with automatic current sharing and n-times gain capability. (August 2022) - Zhao, Lingling; Sun, Min; Guo, Zehui; Dong, Yan; Pan, Siming; Huang, Qi
Abstract: Inspired by the advantages of multiphase series capacitor boost converter, its automatic current sharing and N-times gain control strategy is proposed and investigated. Theoretical analysis is developed through capacitor charge balance and inductance volt-second balance. Then the constraint conditions of operating modes time are obtained to balance the phase current and achieve N-times gain. The final control strategy was obtained by the optimized timing sequence arrangement of the modes. The proposed control strategy is applied in 4-phase series capacitor Boost converter for CCM operation for duty cycle 0 to 1. Without any additional sensors or other devices, the automatic current sharing is achieved. The current of each phase is automatically distributed evenly among the phases, and N-times voltage gain is achieved. Finally, simulation results are given to verify the analysis of the proposed control strategy.